Evaluation of PLGA microspheres with triple regimen on long‐term survival of vascularized composite allograft – an experimental study. (29th January 2020) - Wang, Shoubao; Xiong, Yao; Wang, Yinmin; Chen, Jingting; Yang, Jun; Sun, Binbin
Summary: Systemic immunosuppression is indispensable for vascularized composite allotransplantation (VCA). Daily administration of standard triple therapy regimen of tacrolimus (FK506), mycophenolate mofetil (MMF), and steroid has severe side effects and reduces the compliance of VCA recipients. To overcome these hurdles, FK506/MMF/prednisolone (PDNN) was loaded into PLGA microspheres (PGLA MS). A single injection of FK506/MMF/PDNN‐PLGA MS significantly prolonged the survival time of allograft in a rat hind limb transplantation model with a median survival time (MST) of more than 150 days compared to 34.5 days in the group treated orally with FK506/MMF/PDNN and 11 days in the nontreatment allograft and MS control groups. Analysis of showed that FK506/MMF/PDNN‐PLGA MS could maintain relatively higher plasma and tissue drug concentrations for a long time. Moreover, histopathology and flow cytometry of circulating mononuclear cells revealed significantly prolonged immunosuppression by the FK506/MMF/PDNN‐PLGA MS compared with the orally given FK506/MMF/PDNN. In conclusion, a single injection of FK506/MMF/PDNN‐PLGA MS may provide a new approach for long‐term prevention of immune rejection in VCA.